Tingkat Kecemasan Penderita Penyakit Komorbid Takut Tertular Covid 19 Di Puskesmas Sidomulyo Rawat Jalan Pekanbaru - Trisiwi Kusuma Ningrum; Maswarni Maswarni; Nur Rohmah (Sistem Informasi, 2022)
Comorbidity is a disease experienced by a person. Patients with komorbid diseases are more susceptible to contracting Covid 19 because they experience a decrease in their immune system. The purpose of this study was to find out how the anxiety level of patients with comorbidity fear of contracting Covid 19 at the Sidomulyo Outpatient Health Center Pekanbaru. This type of research is a descriptive study. This research was conducted on August 1-5 2022 at the Raway Health Center Jalan Sidomulyo, Peknabaru. The sampling technique used is accidental sampling with a total sample of 48 respondents. The instrument used in this study was the HARS (Hamilton Ansiaty Rating Scale) anxiety scale questionnaire. The results showed that the anxiety level of respondents at the Sidomulyo Outpatient Public Health Center Pekanbaru was the majority in the moderate anxiety, level category as many as 23 respondents (23%), while respondents who experienced severe anxiety levels were 19 people (39.6%) and those who experienced mild anxiety levels were 4 respondents (8.3%) and 2 respondents (4.2%). Respondents are expected to do more social activities, worship activities that build a sense of comfort, provide peace and avoid anxiety so that their health is always well maintained.